Avaliação in vitro das atividades antioxidante, antimicrobiana e citotóxica de extratos orgânicos das cascas da do fruto jabuticaba (Myrciaria cauliflora Berg) - Coelho, Jéssica Aparecida (2017)
Currently, research related to natural products, mainly those of plant origin, has been strongly encouraged by the World Health Organization (WHO), once the use of plants with proven or unproven medicinal properties are of great influence on public health. Among the high medicinal potential plants, the species Myrciaria cauliflora Berg, which belongs to the Myrtaceae family, popularly known as `Jabuticaba`, a typical Brazilian fruit, is used in popular medicine to treat angina pectoris, dysentery, inflammation and asthma. Aiming to highlight the importance of the use of plants for the treatment of various diseases, the aim of this work was to identify the bioactive compounds present in Jabuticaba peel, and to perform in vitro tests of antioxidant action, antimicrobial potential and cytotoxic effect against red blood cells. The tests were carried out with the aim of obtaining results that could prove the possible pharmacological activities of the organic extracts, for further development of formulation with the use of pharmaceutical technology. Bioprospecting studies from the Brazilian flora represent concrete possibilities in the discovery of new antimicrobial agents, as well as the improvement and the discovery of new technologies in the most diverse industrial branches, with emphasis in the health sector.